Uncertainty analysis of motion accuracy on single-axis feed drive systems - Li Quan; Wanhua Zhao (Advances in Mechanical Engineering, 2024)
The use of mechatronic integrated equipment, such as servo feed drive systems, has become increasingly important in high-end manufacturing, aerospace, and semiconductor industries. However, while advancements in modeling and analysis have improved deterministic feed systems, there is a lack of research into uncertain motion accuracy due to random factors in actual working conditions. This paper aims to address this issue by analyzing the uncertainty of motion accuracy in single-axis feed drive systems. Random factors already impact both positioning accuracy and repeatability, while dynamic errors are reflected in the mean and variance of following errors. The study also considers the impact of disturbance uncertainty, parameter uncertainty, and model uncertainty on motion accuracy. To investigate the impact of these sources of uncertainty on a six-degree-of-freedom linear motor feed system, a simulation example using the Monte Carlo simulation algorithm was utilized. The analysis revealed that uncertainty indeed has an impact on motion accuracy. This research will help identify and improve random errors in servo feed systems, ultimately leading to the development of strategies for reducing motion accuracy uncertainty and enhancing the accuracy and reliability of feed systems in high-end manufacturing, aerospace, and semiconductor industries.